The difficulty in the applicability of the International Financial Reporting Standards IFRS in the context of the territorial entities (2017)
The globalization of markets and the internationalization of the economy have meant that in the world of business and transactions one speaks in the same language, in order to comply with this requirement, it is necessary to establish guidelines or parameters to be governed Not only the companies but also the public entities of each country. From this need is born the establishment of a normative framework in Colombia which is guided by the International Financial Reporting Standards IFRS and in the case of the public sector the International Accounting Standards IPSAS, with these normative frameworks it seeks to strengthen accounting and financial practices Of public entities under international reference frameworks and in the search for better executions, allowing to reflect total transparency in the relation to the financial scope of public entities. Although every change is made with the aim of always improving a situation, its implementation brings with it a series of difficulties that causes the process to be carried out more slowly and the results not obtained in the expected time. In the case of the Public Sector, it is evident in the Property, Panta and Equipment and accounts receivable mainly.